Emerging thermal processes in the food industry : unit operations and processing equipment in the food industry - Jafari, Seid Mahdi (Woodhead Publishing, 2022)
Emerging Thermal Processes in the Food Industry, a volume in the Unit Operations and Processing Equipment in the Food Industry series, explains the processing operations and equipment necessary for thermal processing, including infrared heating, microwave processing, sonication, UV processing, ohmic heating and dielectric processing. These processes and unit operations are very important in terms of achieving favorable sensory properties and energy usage. Chapters emphasize basic texts relating to experimental, theoretical, computational and/or applications of food engineering principles and relevant processing equipment for emerging thermal unit operations.